REVIEW OF THE FINDINGS ON THE INITIAL LEVEL OF THE FUTURE DOCTORS’ SUBJECT COMPETENCIES IN MEDICAL DEONTOLOGY IN TERMS OF MOTIVATIONAL COMPONENT - Olena Holik (European Scientific Journal, ESJ, 2014)
Our research is dedicated to the problem of the development of the future doctors’ subject competencies in Medical deontology by means of Cooperative learning structures. In this article we are going to review the findings on the initial level of the future doctors’ subject competencies in Medical deontology in terms of the motivational component within the framework of the experimental part of the investigation. Our main task is to reveal the gaps in the motivational component of the future doctors’ subject competencies in Medical deontology and to suggest Cooperative learning as a technique to improve the deontological education. The initial level of the development of the future doctors’ subject competencies in Medical deontology has been evaluated by us in terms of three components – motivational, cognitive and behavioral the essence of which is represented in criteria and the latter are reflected in indicators. In this article we will review the findings on the motivational component. The initial level of the development of the motivational component of the competencies in Medical deontology has been determined in terms of the professional needs and interests of the medical students, the indicators of which include awareness of a career choice, type of motivation to study at the higher medical educational establishment (“professional” motives, motives of “personal prestige”, “pragmatic” and “educational” motives, external factors), prevailing personality orientation (humanistic, professional, social, business, and antisocial), motivation for communication, self-improvement and selfdevelopment motivation, recognition of the practical significance of the academic course “Deontology in medicine”, an interest in ethical and deontological education.